Selective Electrooxidation of Biomass‐Derived Alcohols to Aldehydes in a Neutral Medium: Promoted Water Dissociation over a Nickel‐Oxide‐Supported Ruthenium Single‐Atom Catalyst. (25th February 2022) - Ge, Ruixiang; Wang, Ye; Li, Zezhou; Xu, Ming; Xu, Si‐Min; Zhou, Hua; Ji, Kaiyue; Chen, Fengen; Zhou, Jihan; Duan, Haohong
Abstract: The biomass‐derived alcohol oxidation reaction (BDAOR) holds great promise for sustainable production of chemicals. However, selective electrooxidation of alcohols to value‐added aldehyde compounds is still challenging. Herein, we report the electrocatalytic BDAORs to selectively produce aldehydes using single‐atom ruthenium on nickel oxide (Ru1 ‐NiO) as a catalyst in the neutral medium. For electrooxidation of 5‐hydroxymethylfurfural (HMF), Ru1 ‐NiO exhibits a low potential of 1.283 V at 10 mA cm −2, and an optimal 2, 5‐diformylfuran (DFF) selectivity of 90 %. Experimental studies reveal that the neutral electrolyte plays a critical role in achieving a high aldehyde selectivity, and the single‐atom Ru boosts HMF oxidation in the neutral medium by promoting water dissociation to afford OH*. Furthermore, Ru1 ‐NiO can be extended to selective electrooxidation of a series of biomass‐derived alcohols to corresponding aldehydes, which are conventionally difficult to obtain in the alkaline medium. Abstract : Selective oxidation of 5‐hydroxymethylfurfural (HMF) to produce 2, 5‐diformylfuran (DFF) was achieved in neutral medium over single‐atom Ru supported on NiO (Ru1 ‐NiO). Single‐atom Ru sites boost HMF oxidation by facilitating water dissociation, which generates electrophilic OH* as a key reactant. The substrate scope was extended to produce aldehydes from various biomass‐derived alcohols. Key: Ni (light gray), Ru (green), O (red), C (dark gray), H (white).